2006
DOI: 10.1590/s1413-86702006000600010
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis during peginterferon-alpha2a and ribavirin therapy: case report

Abstract: Pegylated Interferon-alpha, combined with ribavirin, gives high sustained virological response in patients with hepatitis C virus, an important public health problem and one of the most frequent chronic infectious diseases worldwide. Though it has therapeutic benefits, treatment with IFN-alpha may be complicated by various side effects, especially symptoms of major depression and acute mania. Psychosis is a rare side effect, and its management usually includes discontinuation of IFN-alpha. We report a case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
6
1
1
Order By: Relevance
“…In contrast, previous reports suggest that interferon therapy negatively affects HRQOL of patients with chronic hepatitis C during the initial 12-24 weeks of treatment and is associated with several psychiatric and neurological side effects [Neary et al, 1999;Quarantini et al, 2006aQuarantini et al, , 2006bQuarantini et al, , 2007. Importantly, the present results were not influenced by the patients or the clinician knowledge of the response to treatment, since both were blind to the HCV polymerase chain reaction status.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast, previous reports suggest that interferon therapy negatively affects HRQOL of patients with chronic hepatitis C during the initial 12-24 weeks of treatment and is associated with several psychiatric and neurological side effects [Neary et al, 1999;Quarantini et al, 2006aQuarantini et al, , 2006bQuarantini et al, , 2007. Importantly, the present results were not influenced by the patients or the clinician knowledge of the response to treatment, since both were blind to the HCV polymerase chain reaction status.…”
Section: Discussioncontrasting
confidence: 85%
“…Other authors who have also used a standardized diagnostic interview have demonstrated that depression is associated with low SF-36 scores; although in these studies HCV-infected patients undergoing treatment with IFN were not excluded, which could have interfered negatively in the assessment of HRQOL and increased the incidence of psychiatric events [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Psicose que é um raro sintoma relacionado ao tratamento imuno-modulatório, foi evidenciada em estudo caso controle de pacientes com hepatite C que fizeram uso terapêutico de interferon (IFN) recombinante (QUARANTINI et al, 2006).…”
Section: Resultsunclassified